Developing Marketing Strategies Based on Segmentation, Targeting, and Positioning (STP) and Marketing Mix Analysis: A Case Study in Jernip Kencana - Salma Yusoluna; Novika Candra Astuti (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
Jernip Kencana is a family-owned MSME established in 1996 in Kuningan, West Java, producing natural lime syrup with consistently high customer ratings (4.2–4.8 out of 5). Despite strong product quality and long-standing market leadership, the company experienced a significant 61.7% decline in sales, from 922 units in Q2 2021 to 353 units in Q4 2024, indicating serious marketing challenges. This study aims to identify the causes of declining sales and to formulate an integrated marketing strategy by analyzing customer segmentation, targeting and positioning (STP), as well as internal and external business environments. Using a mixed-method approach, primary data were collected through in-depth interviews, observations, and questionnaires from 285 respondents, complemented by secondary data. Analytical tools included K-means clustering, VRIO, PESTLE, Porter’s Five Forces, TOWS, and the Marketing Mix 7Ps. The findings reveal key issues such as weak brand visibility, lack of clear STP, limited digital marketing capability, absence of customer data management, and dependence on aging distributors. The study proposes a “Heritage Premium Natural Wellness” positioning, targeting the Wellness Advocates segment, supported by strategic adjustments in STP, marketing mix, and a phased implementation plan. This research offers practical insights for traditional MSMEs navigating digital-era competition.